La difficile quête d'un système de sécurité en Europe : les limites de l'approche institutionnelle - Braillard, Philippe (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1995)
With the end of the cold war, Europe, whilst avoiding the major threat of a global conflagration, has entered a period of uncertainty and instability, resulting from new risks which have appeared and from conflicts which have developed to the east of the continent. The institutions which were created in the context of the cold war, and which helped to manage it, are now forced to redefine their objectives and strategies, since they were not suited to deal with a profoundly different situation. This study evaluates the manner in which these new security challenges have been addressed through adaptation of the various institutions active in the field of security. The study shows that these various adaptations have been incapable of bringing effective answers to the new security problems which have appeared on the continent. Finally, based on this analysis, the study tries to identify the potential and limits of each of these institutions in the search for a European security System.